2016
DOI: 10.1186/s40064-016-3708-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting RFID adoption in the agricultural product distribution industry: empirical evidence from China

Abstract: We conducted an exploratory investigation of factors influencing the adoption of radio frequency identification (RFID) methods in the agricultural product distribution industry. Through a literature review and field research, and based on the technology–organization–environment (TOE) theoretical framework, this paper analyzes factors influencing RFID adoption in the agricultural product distribution industry in reference to three contexts: technological, organizational, and environmental contexts. An empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 18 publications
(12 reference statements)
3
51
4
Order By: Relevance
“…When users feel that they don't have much control over the outcome of a system, they become increasingly suspicious about that system [107]. From companies' point of view, they will be less likely to adopt a new technology if they see it as very complex and incompatible with their present technologies and practices [108].…”
Section: Hypotheses Development Of Complexitymentioning
confidence: 99%
“…When users feel that they don't have much control over the outcome of a system, they become increasingly suspicious about that system [107]. From companies' point of view, they will be less likely to adopt a new technology if they see it as very complex and incompatible with their present technologies and practices [108].…”
Section: Hypotheses Development Of Complexitymentioning
confidence: 99%
“…Incidentally, developing countries like Africa discussed advanced topics like maintaining cold chain integrity (Goedhals et al, 2017). Meanwhile, Shi and Yan (2016) discussed the factors affecting Radio Frequency Identification (RFID) adoption in the agricultural product distribution industry in China. They identified factors using technology, organisation, and environmental framework regarding the RFID adoption that can be used for future references.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, companies should start adopting modern cold chain technologies like RFID and the like. Specifically, adopting these technologies allowed for a more transparent and effective business model because, in CLSC, the idea was all about the constant maintenance for the correct temperature to avoid breaks (Qi et al, 2014;Shi & Yan, 2016). Hence, failure to adopt these technologies could result in temperature breaks and damaging the cold chain products and suffering loss.…”
Section: What Is the Status Of Modern Cold Chain Technology Adoption?mentioning
confidence: 99%
“…Therefore, this study relies on its exploration, drivers and CSFs currently identified in the literature from different industries, e.g. in health-care, (Janz, Pitts, and Otondo, 2005;Yue et al, 2008;Vanany and Shaharoun, 2008;Ting, Kwok, Tsang, and Lee, 2009), manufacturing (Fish and Forrest, 2006;Attaran, 2007;Ngai et al, 2012) and retail (Reyes and Jaska, 2005;Shi and Yan, 2016), as shown in Table I. The critical factors can broadly be divided into three categories:…”
Section: Jedt 173mentioning
confidence: 99%